2020
DOI: 10.1080/10408398.2020.1803200
|View full text |Cite|
|
Sign up to set email alerts
|

Selenium status in the body and cardiovascular disease: a systematic review and meta-analysis

Abstract: Background: Both experimental and observational studies have provided conflicting evidence on the associations of selenium with incidence and mortality of cardiovascular disease (CVD). The aim of this study was to evaluate the association between selenium status in the body and incidence and mortality of CVD by performing a systematic review and meta-analysis of observational studies and randomized controlled trials. Methods: A systematic search for articles in MEDLINE (Ovid), Embase, Web of Science (Thomson R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 44 publications
2
47
0
2
Order By: Relevance
“…A recent meta-analysis reported a 50% increase in Se concentration to be associated with 24% reduction in the risk of developing ischaemic heart disease [78]. A similar conclusion was drawn by a study that reported a reduced risk of CVD (RR: 0.66, 95% CI: 0.40-1.09) and mortality (RR: 0.69, 95% CI: 0.57-0.84) in individuals with high Se status [79]. Also, UK and Denmark PRECISE randomised, double-blinded, placebo-controlled, clinical trials explored the effects of Se supplementation on total cholesterol (T-C) and non-HDL cholesterol [80,81].…”
Section: Se Supplementation In Adults and The Elderly Populationsupporting
confidence: 53%
“…A recent meta-analysis reported a 50% increase in Se concentration to be associated with 24% reduction in the risk of developing ischaemic heart disease [78]. A similar conclusion was drawn by a study that reported a reduced risk of CVD (RR: 0.66, 95% CI: 0.40-1.09) and mortality (RR: 0.69, 95% CI: 0.57-0.84) in individuals with high Se status [79]. Also, UK and Denmark PRECISE randomised, double-blinded, placebo-controlled, clinical trials explored the effects of Se supplementation on total cholesterol (T-C) and non-HDL cholesterol [80,81].…”
Section: Se Supplementation In Adults and The Elderly Populationsupporting
confidence: 53%
“…Metaanalysis involving 16 prospective studies demonstrated an inverse relationship between Se status and cardiovascular risk (43). Likewise, a systematic review with meta-analysis involving 13 studies revealed that high physiological levels of Se are associated with lower incidence and lower mortality from cardiovascular disease (CVD) (44). In another meta-analysis in which more than 40 thousand participants in randomized clinical trials were included, the authors found that Se supplementation decreases the serum levels of C-reactive protein and increases the levels of GPX, suggesting a positive effect on reduction of inflammation and oxidative stress in cardiovascular diseases (45).…”
Section: Selenium and Diseasesmentioning
confidence: 99%
“…Deprivation of Se was strongly correlated with cardiomyopathy occurring in countries with significantly reduced Se intake [104]. Multiple studies have been conducted to evaluate Se's effect on CVD risk [105][106][107].…”
Section: Se and Cardiovascular Diseasesmentioning
confidence: 99%